Post-vaccination surveillance and molecular epidemiology of highly pathogenic H5N1 avian influenza in Vietnam : a thesis presented in partial fullfilment [sic] of the requirements for the degree of Master of Veterinary Studies at Massey University, Institute of Veterinary, Animal and Biomedical Sciences, Massey University, Palmerston North, New Zealand - Nguyen, Thi Diep (Massey University, 2011)
Abstract not available
Keywords: Avian influenza; Bird flu; H5N1 influenza; Molecular epidemiology; Post-vaccination surveillance; Vietnam